A preliminary research study on the cytotoxicity of expired and non-expired composite resins : in vitro study = Estudio preliminar in vitro de la citotoxicidad de resinas compuestas caducadas y no caducadas - Kazak, Magrur
Objective: Studies have focused on use of non-expired composites. Unfortunately some clinicians still use expired composite resins without considering their effects. The objective of this in vitro preliminary research was to investigate cytotoxicity of expired(6-months) and non-expired composite resins. Materials and methods: Expired (E) and non-expired (NE) samples of one bulk-fill (Tetric N-Ceram Bulk-fill [TNB], Ivoclar Vivadent), two nano-hybrid (Tetric N-Ceram [TN], Ivoclar Vivadent; Clearfil Majesty ES-2 [CM], Kuraray) composite resins were tested on L929 fibroblast cells. Medium covering cells was removed then plastic rings (2-mm height) were filled with non-polymerized composite resins, placed in direct contact with cells and polymerized with LED light curing unit (LCU). Three samples were prepared for each group. After polymerization, removed medium was added to the cells. Cells that were left without medium (WOM) and cells that were exposed to LCU were used as positive control groups. Cells without any treatment were used as negative control group (C). Cells were incubated with tested materials for 7-days to evaluate cytotoxicity. Cell viability was calculated by sulforhodamine B test as a percentage (%). One-way ANOVA and post-hoc Tukey tests were used for statistical analyses (p<0.05). Results: Comparison between E and NE groups of same composite resins did not result in statistically significant differences (p>0.05), except between TN NE and TN E (p<0.05). TN E group was significantly more cytotoxic than TN NE group. When NE composite resin groups were compared to each other, statistically significant difference was only obtained between TNB NE and TN NE (p<0.05). Among all tested groups, TN NE group showed the least cytotoxic profile. No statistically significant differences were determined when E composite resin groups were compared to each other (p>0.05). All experimental groups compared with C group showed statistically significant...